2011
DOI: 10.1093/infdis/jir379
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of a Bivalent Recombinant Vesicular Stomatitis Virus Vaccine in the Syrian Hamster Model of Lethal Ebola Virus Infection

Abstract: Bivalent VSV vectors are a feasible approach to vaccination against multiple pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 33 publications
2
52
1
1
Order By: Relevance
“…27 , 49 , 50 In addition, a dual VSV-based vector expressing the GPs of viruses from two different virus families was shown to protect against both viruses in an animal model with similar short time to protection and post-exposure efficacy as VSV-EBOV. 18 , 51 Now that the safety, efficacy, and feasibility of the VSV platform have been proven, it is time to finally license this platform, as has been recently done in Russia. In addition, moving VSV-based vaccines for other pathogenic viruses with outbreak potential, such as MARV, LASV, and Nipah virus, forward to clinical trials should be a priority.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 , 49 , 50 In addition, a dual VSV-based vector expressing the GPs of viruses from two different virus families was shown to protect against both viruses in an animal model with similar short time to protection and post-exposure efficacy as VSV-EBOV. 18 , 51 Now that the safety, efficacy, and feasibility of the VSV platform have been proven, it is time to finally license this platform, as has been recently done in Russia. In addition, moving VSV-based vaccines for other pathogenic viruses with outbreak potential, such as MARV, LASV, and Nipah virus, forward to clinical trials should be a priority.…”
Section: Resultsmentioning
confidence: 99%
“…In a post-exposure study, all hamsters in the groups treated immediately or 24 hours after challenge survived, while all hamsters treated 48 hours after challenge succumbed to MA-EBOV infection. 18 …”
Section: Introductionmentioning
confidence: 99%
“…13 Other preclinical studies also demonstrated a rapid and significant protection in NHPs. 12,14,[48][49][50][51][52] The first 3 open-label, uncontrolled, phase I clinical trials of rVSV-EBOV vaccine were conducted in Lambar en e, Kilifi, and Hamburg, respectively, which were designed to assess the safety, and immunogenicity of escalating doses ranging from 3 £ 10 5 to 2 £ 10 7 vp in early 2014 (NCT02283099, NCT02287480, NCT02296983) ( Table 1). 53 The preliminary results of the rVSV-EBOV vaccine from the above 3 trials, involving a total of 99 participants, demonstrated a good immunogenicity, but a mild to moderate reactions related to vaccination (Table 4).…”
Section: Rvsv-ebovmentioning
confidence: 99%
“…The protective potential of the rVSV vaccine against ZEBOV infection has been demonstrated extensively in rodents [6567] and also in NHPs showing that a single dose can protect animals from lethal disease 4 weeks post-immunzation [68]. The animals were completely protected from disease and did not develop detectable ZEBOV viremia.…”
Section: Replication-competent Vaccine Vectorsmentioning
confidence: 99%